Transient Voltage Programming in Electric Power Grounding System. Issue 1 (February 2021) - Syafruddin, R; Herawati, YS; Ramady, Givy Devira; Hidayat, Wisnu; Lestari, Ninik Sri; Anung,
Abstract: Liner equations with n variables can be solved if there are n equations, the matrix is formed n x n square matrix, using the inverse matrix method. In this research, the linear equation used comes from the rod and mesh grounding system method, which is solved by the finite element method to calculate the grounding impedance, from the results of other research researchers. Here the researcher wants to inform in this study how to solve the linear equation with a calculation program. And the research results are plotted in Cartesian coordinates V = V (t). The results of this calculation program can be used to estimate how much the transient voltage is in the ground rod / mesh in the place where the electrical power system substation will be built when lightning strike with an amplitude of 34 kA/switching with a current of 34 kA/step with a current of 34 kA crash it. To adjust the transient voltage by adjusting the length of the finite element, required in accordance with the applicable safety level, while the subsequent arrangement can by increasing the number of mesh or increasing the length of the mesh.